2015
DOI: 10.1016/j.forsciint.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of uranium compounds and the use of multivariate analysis for visualization and classification

Abstract: Raman spectroscopy was used on 95 samples comprising mainly of uranium ore concentrates as well as some UF4 and UO2 samples, in order to classify uranium compounds for nuclear forensic purposes, for the first time. This technique was selected as it is non-destructive and rapid. The spectra obtained from 9 different classes of chemical compounds were subjected to multivariate data analysis such as principal component analysis (PCA), partial least square-discriminant analysis (PLS-DA) and Fisher Discriminant Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Adding a nearby H-bonded water molecule shifts the frequency bycompared to the measured value of 109.0 meV. This phenomenon has been observed in a variety of other water-containing uranyl species, such as uranyl hydroxide, ammonium diuranate, ammonium uranyl carbonate, sodium diuranate, and uranyl acetate 4547 . This mechanism of H-bonding damping may be responsible for the line shape of uranyl stretching vibrations.…”
Section: Water Couplingmentioning
confidence: 51%
“…Adding a nearby H-bonded water molecule shifts the frequency bycompared to the measured value of 109.0 meV. This phenomenon has been observed in a variety of other water-containing uranyl species, such as uranyl hydroxide, ammonium diuranate, ammonium uranyl carbonate, sodium diuranate, and uranyl acetate 4547 . This mechanism of H-bonding damping may be responsible for the line shape of uranyl stretching vibrations.…”
Section: Water Couplingmentioning
confidence: 51%
“…Ho et al reported a spectrum from a 'UF 4 ' sample provided by the International Atomic Energy Agency (λ ex = 785 nm) with prominent bands around 860 and 400 cm À1 that were attributed to UF 4 . [20] The spectrum most likely represented a combination of aging and decomposition products. The band located around 860 cm À1 was most likely because of a uranyl compound such as uranyl fluoride.…”
mentioning
confidence: 99%
“…The process occurs by addition of oxalic acid to uranyl nitrate, forming an intermediate oxalate precipitate, which is calcined to uranium oxide (U 3 O 8 ) for eventual storage. Other intermediates exist, such as uranyl peroxide ([(UO 2 )(O 2 )(H 2 O) 2 ]•2H 2 O), which is produced following a similar processing route and has been extensively studied for its material properties [2][3][4][5][6]. Furthermore, some recent characterisations have been focused on the nuclear forensic implications of uranyl peroxides and its oxides [7].…”
Section: Introductionmentioning
confidence: 99%